2007
DOI: 10.1093/nar/gkl1009
|View full text |Cite
|
Sign up to set email alerts
|

ViTa: prediction of host microRNAs targets on viruses

Abstract: MicroRNAs (miRNAs) are involved in various biological processes by suppressing gene expression. A recent work has indicated that host miRNAs are also capable of regulating viral gene expression by targeting the virus genomes. To investigate regulatory relationships between host miRNAs and related viruses, we present a novel database, namely ViTa, to curate the known virus miRNA genes and the known/putative target sites of human, mice, rat and chicken miRNAs. Known miRNAs are obtained from miRBase. Virus data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(66 citation statements)
references
References 12 publications
(18 reference statements)
3
61
0
1
Order By: Relevance
“…Lower minimum free energy (MFE) values of the miRNAs and the target sites revealed energetically more probable hybridizations between miRNAs and target genes (21). Our in silico analysis suggested a putative binding site for miR-181c in the HCV E1 and NS5A genes, with lower MFE values of Ϫ20.2 and Ϫ18.2, respectively (Fig.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Lower minimum free energy (MFE) values of the miRNAs and the target sites revealed energetically more probable hybridizations between miRNAs and target genes (21). Our in silico analysis suggested a putative binding site for miR-181c in the HCV E1 and NS5A genes, with lower MFE values of Ϫ20.2 and Ϫ18.2, respectively (Fig.…”
Section: Resultsmentioning
confidence: 77%
“…Since overexpression of miR-181c downregulates HCV replication, we performed in silico analyses with ViTa algorithms (21) to identify whether miR-181c physically binds to the HCV genome. Lower minimum free energy (MFE) values of the miRNAs and the target sites revealed energetically more probable hybridizations between miRNAs and target genes (21).…”
Section: Resultsmentioning
confidence: 99%
“…Identification of functional target sequences of hsa-miR-296-5p is necessary in order to define the regulatory mechanism of EV71 infection by this miRNA. By using ViTa algorithms (35) to predict viral targets of human miRNA, our analysis showed that the P1 region of the EV71 genome carries two putative hsa-miR-296-5p binding sites (nt 2115 to 2135 and nt 2896 to 2920) ( Fig. 4A and B).…”
Section: Ev71 Infection Upregulates Expression Of Hsa-mir-296-5pmentioning
confidence: 99%
“…miR-199a-5p Directly Targets Ets-1 by Interacting with the 3Ј UTR-To delineate the mechanisms underlying the angiostatic effect, bioinformatics analyses were performed to investigate the possible direct target using algorithms including Targetscan (22), Pictar (23), MiRanda (22), and miRDB (24). In silico analysis revealed that Ets-1 3Ј-UTR contains a highly conserved binding site at positions 2708 -2714 for miR-199a-5p ( Fig.…”
Section: Mir-199a-5p Is Angiostatic In Hmecs-mentioning
confidence: 99%